Survey of VPU olympiad 2010 for young mathematicians - Jakaitytė, Eglė; Kaučikas, Algirdas; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2010)
The texts and solutions of the VPU young mathematicians olympiad – 2010 are presented.